Association mapping and candidate genes for physiological non-destructive traits: Chlorophyll content, canopy temperature, and specific leaf area under normal and saline conditions in wheat - Said, Alaa A.; Moursi, Yasser S.; Sallam, Ahmed (Frontiers in Genetics, 2022)
Wheat plants make substantial physiological adaptation when they are exposed to salt stress. Identifying such physiological mechanisms and their genetic control is very important to improve salt tolerance in wheat. In this study, leaf chlorophyll content (CC), leaf canopy temperature (CT), and specific leaf area (SLA) were scored in a set of 153 highly diverse wheat genotypes under normal and salt tolerance. On average, CC and SLA decreased under salt stress, while CT average was higher under salt than control. Under both conditions, CT was negatively and significantly correlated with CC, while no correlation was found between SLA and both CC and CT. High genetic and heritability estimates were found among genotypes for all traits. Genome-wide association study revealed important QTLs for CC under both conditions (10) and SLA under salt stress (four). These QTLs were located on chromosomes 1B, 2B, 2D, 3A, 3B, 5A, 5B, and 7B. All QTLs detected in this study had major effects with R2 extending from 20.20 to 30.90%. The analysis of gene annotation revealed three important candidate genes (TraesCS5A02G355900, TraesCS1B02G479100, and TraesCS2D02G509500) that are found to be involved in the response to salt stress in wheat with high expression levels under salt stress compared to control.